The Connection Between Mode Beliefs and Mode Liking: Biking versus Driving - Susan Handy (Findings)
This paper examines the connection between beliefs about modes and liking of modes using data from the annual Campus Travel Survey at the University of California, Davis. The analysis, which focuses on biking and driving, shows that the beliefs about these modes differ significantly but that in both cases the beliefs that the mode is fun and relaxing are more strongly correlated with liking than other beliefs.